2009
DOI: 10.1093/hmg/ddp190
|View full text |Cite
|
Sign up to set email alerts
|

Toxic tubular injury in kidneys from Pkd1-deletion mice accelerates cystogenesis accompanied by dysregulated planar cell polarity and canonical Wnt signaling pathways

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is characterized by large fluid-filled cysts and progressive deterioration of renal function necessitating renal replacement therapy. Previously, we generated a tamoxifen-inducible, kidney epithelium-specific Pkd1-deletion mouse model and showed that inactivation of the Pkd1 gene induces rapid cyst formation in developing kidneys and a slow onset of disease in adult mice. Therefore, we hypothesized that injury-induced tubular epithelial cell proliferation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
148
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(153 citation statements)
references
References 39 publications
4
148
0
1
Order By: Relevance
“…For the renal cystic phenotype, we previously showed that the renal injury is a trigger that strongly accelerates the polycystic kidney disease. 31 Extensive isometric myographic analysis did also reveal that no difference in response to KCl, acetylcholine, phenylephrin, U46619 or serotonin was observed in young mice (11 weeks) or in older mice (40 weeks), in heterozygous or in homozygous animals with a selective disruption of Pkd1 in SMCs. Only the 40-week-old heterozygous Pkd1 del/ þ mice, which carry a deletion allele in all cells, show a significant increase in vascular contractility in response to phenylephrin.…”
Section: Discussionmentioning
confidence: 96%
“…For the renal cystic phenotype, we previously showed that the renal injury is a trigger that strongly accelerates the polycystic kidney disease. 31 Extensive isometric myographic analysis did also reveal that no difference in response to KCl, acetylcholine, phenylephrin, U46619 or serotonin was observed in young mice (11 weeks) or in older mice (40 weeks), in heterozygous or in homozygous animals with a selective disruption of Pkd1 in SMCs. Only the 40-week-old heterozygous Pkd1 del/ þ mice, which carry a deletion allele in all cells, show a significant increase in vascular contractility in response to phenylephrin.…”
Section: Discussionmentioning
confidence: 96%
“…The role of canonical Wnt signaling in ADPKD has been an area of research. [20][21][22][23][24][25] Increased canonical Wnt signaling [20][21][22] and diminished signal activation or stable β-catenin [23][24][25] that lead to an opposite effect of planar cell polarity/noncanonical signaling have been reported in different ADPKD mouse models. These data suggest renal cystogenesis is initiated by imbalance between canonical and planar cell polarity/ non-canonical signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of this model is that the remaining kidney is untouched and there is no damage to this kidney because of ischemia or nephrotoxins. Previous studies used induction of renal injury with ischemia-reperfusion or a nephrotoxin 9,15,16 to assess accelerated cyst formation. These models involve the repair of renal injury, which is a complex process that involves repopulating damaged renal tubules with regenerated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown accelerated cyst formation after ischemic or nephrotoxic kidney injury. 9,15,16 However, recovery from acute kidney injury is a multifactorial process including loss of normal renal architecture, disruption of cell-tomatrix and cell-to-cell interactions, necrosis, apoptosis, and recruitment of a myriad of hormones and autocoids. 17 Recent studies 18,19 have indicated that the mammalian target of rapamycin (mTOR) 20 may be one important factor that mediates the hypertrophic response to unilateral nephrectomy.…”
mentioning
confidence: 99%